2012
DOI: 10.1100/2012/841375
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Profile in Children and Adolescents with Severe Course Juvenile Idiopathic Arthritis

Abstract: Objective. Juvenile Idiopathic Arthritis (JIA) is the most common chronic pediatric rheumatic disease. It is recognized that only reliance on clinical signs of disease outcome is inadequate for understanding the impact of illness and its treatment on child's life and functioning. There is a need for a multidisciplinary and holistic approach to children with arthritis which considers both physical and emotional functioning. This study investigated the psychosocial functioning of children and adolescent with JIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 14 publications
(23 reference statements)
2
32
0
Order By: Relevance
“…Compromised memory during treatment in patients may have been re‐established after treatment termination, possibly due to neurogenesis in the hippocampus . Our finding that patients and healthy controls did not differ in behavioural problems is consistent with studies of children with juvenile idiopathic arthritis . Studies of children with nephrotic syndrome, however, have reported increased behavioural problems during glucocorticoid treatment .…”
Section: Discussionsupporting
confidence: 88%
“…Compromised memory during treatment in patients may have been re‐established after treatment termination, possibly due to neurogenesis in the hippocampus . Our finding that patients and healthy controls did not differ in behavioural problems is consistent with studies of children with juvenile idiopathic arthritis . Studies of children with nephrotic syndrome, however, have reported increased behavioural problems during glucocorticoid treatment .…”
Section: Discussionsupporting
confidence: 88%
“…[24][25][26][27][28][29] JIA disease duration ranged between 3 months to 15 years in children and 10 to 27 years in adults. [24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] JIA subtype was described in 14 studies: 13 included polyarticular, [24][25][26]30,31,[35][36][37][38][39][40]45,46 11 included oligoarticular, 24,26,30,31,[35][36][37][38][39][40]46 10 included systemic, 25,…”
Section: Population Characteristicsmentioning
confidence: 99%
“…37 There were 4 studies that reported no clinically significant depressive symptoms within their study population. 27,[31][32][33] These studies all used the CDI or BDI, screens that were used to detect prevalence rates of clinically significant symptoms in other studies from 9% to 36%, 24,25,39 but were notable for patient populations from reportedly high socioeconomic levels 27,33 and/or restricted to either non-acute patients 32,33 or patients without comorbid psychiatric diagnoses. 31 Three studies compared JIA patients to healthy controls, of which two found that JIA patients had worse depressive symptoms.…”
Section: Prevalence Of Depressive Symptoms In Jiamentioning
confidence: 99%
“…The reasons for the predominance of the polyarticular form RF (-) are not clear, and although there was German colonization in this region, there is no history of patients with German ancestors in our cohort. On the other hand, it is possible that there may exist sub notification of the oligoarticular form, later diagnoses, preferably consulting the forms with higher joint involvement, a probable hypothesis considering the time between the beginning of symptoms and diagnosis (figure 1B) [18][19][20][21][22][23][24][25][26] . Also noteworthy is the distance from home to the HPM, expressed in kilometers and transport times.…”
Section: Discussionmentioning
confidence: 99%